VALIDATION OF NCCN CRITERIA FOR GENETIC TESTING IN HBOC SYNDROME IN BRAZIL - Silva, Andre Vallejo da; Rocha, José Claudio Casali da; Guarneri, Guilherme Olivetti (Mastology, 2017)
Objective: To identify genetic mutations in BRCA1 and BRCA2 genes in women suspected of HBOC syndrome and to correlate them with NCCN testing criteria to verify its impact on mutation finding rates, as well as to identify the relevant criteria, the frequency and type of found mutations and the relative importance of each NCCN criteria. Methodology: A database with all the cases tested for HBOC by the second author from 2010 to 2016 was built, and the variables of interest were annotated and then analyzed with a statistical package to find the relevant variables. Results: A total of 171 patients was tested and 38 had deleterious mutations (22%). Criteria with significant association to the present mutations were the total numbers of relatives with cancer (p=0.02) and Ashkenazi lineage (p=0.001). Age of the youngest relative with cancer below 49 was not significant in this sample (p=0.1). There is a strong correlation between mutated patients and NCCN criteria (p=0.0001), but we found no such correlation between the presence of NCCN testing criteria and the presence of mutation (p=0.11). Regarding the use of NCCN criteria to find BRCA mutations, sensitivity was 0.947, specificity was 0.068, PPV was 0.225 and NPP was 0.818. Accuracy was 0.263. Conclusion: The incidence of BRCA1 and BRCA2 deleterious mutations in our study was similar to that found in other populations. NCCN criteria were a poor predictor of deleterious mutation in BRCA1 and BRCA2 in general, although most mutant patients had at least one NCCN testing criteria, specially increasing number of affected relatives and Ashkenazi lineage.